«Morții cer de băut»: Il meccanismo della successione in Romania tra normatività ed eteroprassi nella tradizione cristiano ortodossa - Girneata, Simona Fabiola (Dopo di noi, 2025)
The complex regulatory mechanism that regulates hereditary succession in Romania requires a holistic analysis that combines legal and anthropological studies, as well as theological and historical insights. In fact, this mechanism is strongly influenced today not only by the Orthodox Christian religion, but also by pagan practices. These practices have passed into obscurity over time, labeled as historically «religious» practices, and yet they intertwine spiritual and social aspects in the management of inheritances and in the rites of commemoration of the deceased. In the Orthodox religion, the link between the visible and the invisible, between the earthly world and the afterlife, plays a decisive role. For this reason, the will of the deceased never remains an ossified artifact of the past, but a future projection that accompanies the life of those left behind. In order to interpret the wishes expressed in wills, people often rely on dreams, everyday signs and, above all, the ritual of the "pomana mortului". This ritual, which obliges the heir to honor the wishes of the deceased, is sometimes expressly requested in wills as a "condicio sine qua non" for becoming a legitimate heir. Contrary to what one might expect, the guarantor of this fulfilment is almost never a legal professional, but a «practitioner of the sacred», so to speak. In many rural areas, priests are often called upon to intervene to ensure that the wishes of the deceased are respected, acting as mediators between family members and the guardians of the succession and testamentary rites. In some cases, the priest becomes fundamental in preventing family conflicts, as he is perceived to provide protection against possible inheritance disputes. The inheritance system in Romania therefore reflects an interweaving of religious traditions and family ties that is not limited to the normative management of assets, giving a particular colouring to the legal concept of «continuity of the deceased’s legal personality». The «figure» of the deceased is not just a memory of the past but continues to live on in religious traditions. Respecting their wishes is seen as a perpetual commitment that extends into the future. The link between the visible and the invisible, and the centrality of the Church in the inheritance process create a complex system in which Orthodox religious tradition and normative inheritance practices intertwine, maintaining a world view in which «here» and «elsewhere» are closely connected.